2017
DOI: 10.1111/jcmm.13251
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐containing extracellular vesicles released from endothelial colony‐forming cells modulate angiogenesis during ischaemic retinopathy

Abstract: Endothelial colony‐forming cells (ECFCs) are a defined subtype of endothelial progenitors that modulate vascular repair and promote perfusion in ischaemic tissues. Their paracrine activity on resident vasculature is ill‐defined, but mediated, at least in part, by the transfer of extracellular vesicles (EVs). To evaluate the potential of isolated EVs to provide an alternative to cell‐based therapies, we first performed a physical and molecular characterization of those released by ECFCs. Their effects upon endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…Furthermore, ECFCs stimulated retinal regeneration by supporting the vascular development promoted by bone marrow-derived CD34 hematopoietic stem cells, as recently demonstrated in a murine model of OIR [ 80 ]. A follow-up study revealed that the injection of ECFCs-derived extracellular vesicles restored the vascular network in a murine model of OIR by stimulating local angiogenesis through the delivery of a package of multiple microRNAs (miRNAs) [ 81 ]. Finally, a recent preclinical study evaluated some parameters that are crucial to support the clinical translation of ECFCs-based therapy in human patients.…”
Section: Endothelial Colony-forming Cells: Origin Mechanisms Of Amentioning
confidence: 99%
“…Furthermore, ECFCs stimulated retinal regeneration by supporting the vascular development promoted by bone marrow-derived CD34 hematopoietic stem cells, as recently demonstrated in a murine model of OIR [ 80 ]. A follow-up study revealed that the injection of ECFCs-derived extracellular vesicles restored the vascular network in a murine model of OIR by stimulating local angiogenesis through the delivery of a package of multiple microRNAs (miRNAs) [ 81 ]. Finally, a recent preclinical study evaluated some parameters that are crucial to support the clinical translation of ECFCs-based therapy in human patients.…”
Section: Endothelial Colony-forming Cells: Origin Mechanisms Of Amentioning
confidence: 99%
“…Medina et al using a murine model of retinal ischemia, demonstrated that ECFC could incorporate into the retinal microvascular tube network and promote vascular repair ( 95 ). ECFC might also exert a vasoregenerative effect in ischemic retinopathies via a paracrine way, mediated at least in part by extracellular vesicles containing microRNA that promote angiogenesis ( 96 ). Optimization studies of ECFC for cell therapy have identified a low dose of ECFC which was effective both by local intravitreal injection and systemic intracarotid delivery, without any significant toxicity ( 97 ).…”
Section: Ecfc For Autologous Cell Therapy For Vascular Repairmentioning
confidence: 99%
“…In the cytoplasm, by Watson-Crick base pairing, the seed region of microRNA guides the RISC to the 3' untranslated region (3'UTR) of target gene transcripts and subsequent silencing of gene expression by facilitating the degradation of messenger RNA (mRNA) and/or suppressing the translational machinery [43]. In addition to autonomously regulating gene expression, a growing body of evidence further supports the role of microRNAs in exerting paracrine effects via extracellular vesicles or exosomes and subsequently modulating the biological functions of a targeted organ [44][45][46]. Given the roles of microRNAs in fine-tuning gene expression in cells, and that the circulating microRNA landscape is contingent on active export from cells and/or passive release from damaged or necrotic cells, it is conceivable that the composition of circulating microRNAs may reflect physiological status and may contain valuable pathobiological information of different disease states.…”
Section: Micrornas the Small Nucleotides That May Play Big Roles In mentioning
confidence: 99%